Hospital discharge information communication and prescribing errors: a narrative literature overview. Issue 1 (10th June 2015) - Mills, Pamela Ruth; Weidmann, Anita Elaine; Stewart, Derek
Abstract : Objectives: To provide a narrative overview of the literature on discharge information communication and medicines discharge prescribing error rate in the UK and other similar healthcare systems. Methods: A narrative review of the peer reviewed literature (2000–2014) on communication of discharge information from hospitals to general practitioners. Databases included were MEDLINE, EMBASE, Cumulative Index to Nursing and Allied Health Literature, Applied Social Sciences Index and Abstracts, and International Pharmacy Abstracts database. Results: The search yielded 673 results with 15 papers satisfying all inclusion criteria. Direct comparison of studies was not feasible due to differences in study populations and outcome measures. No studies reported post Hospital Electronic Prescribing and Medicine Administration (HEPMA) implementation. Studies (n=6) investigating handwritten discharge communication systems demonstrated medicine information inaccuracy ranging from 0.81 errors per patient to 17.5% medicines with errors and 67% letters missing medicines change information; with 77% assessed as legible. Studies (n=4) comparing interim electronic solutions with traditional showed variable results: improved, unchanged or decreased medicine information accuracy. Studies researching solely interim electronic solutions (n=5) with one including prescribing error rate assessment at 8.4% of prescribed items and identification of a new electronic system-related error type. Conclusion: Implementation of interim electronic discharge solutions resulted in complete legibility but did not eradicate information and prescribing errors. A paucity of information is available about HEPMA implementation impact on discharge information communication and prescribing error rates. There is urgent need for formal evaluation in this area.